AGROTOURISM AS AN ALTERNATIVE TO THE SOCIO-ECONOMIC DEVELOPMENT OF RURAL TERRITORIES - B.T. Mataeva,; A.K. Zhuspekova,; G.K. Zambinova,; A.R. Ibraeva,; M.К. Zhetpisbayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
The main problems highlighted are those related to the development of the labor market and nonagricultural employment. The authors proposed directions for the development of alternative employment for rural residents, including through the comprehensive socio-economic development of the village, the formation of a favorable living environment. The popularity of rural tourism is largely due to the desire of urban residents to relax in a relaxed atmosphere in isolation from the bustle of the city and in an environment characterized by more favorable climatic and environmental conditions. The relevance of the topic of this article is due to the fact that at present, the problems of rural development associated with the degradation of agriculture, the lack of optimal working conditions in this area and the depreciation of rural labor are becoming increasingly acute.